Does Ideological Religiosity Influence Academic Achievement? Insights from Structural Equation Modeling - Usman, Muslim (LITPAM, 2025)
This study investigates whether ideological religiosity directly influences academic achievement among Diploma III (D-III) Health students in Aceh, Indonesia. Ideological religiosity represents the internalized dimension of belief, encompassing convictions about divine omniscience, scriptural truth, moral accountability, and prophetic ethical models. Although religious belief is often assumed to shape students’ discipline, responsibility, and academic orientation, empirical evidence regarding its direct impact on academic outcomes remains mixed. Using a quantitative, cross-sectional design, data were collected from 412 students selected through simple random sampling. Ideological religiosity was measured using a five-item validated scale, while academic achievement was operationalized through cumulative grade point average (CGPA). Structural Equation Modeling (SEM) was employed to assess both the measurement and structural models. Confirmatory Factor Analysis (CFA) demonstrated excellent model fit, indicating that ideological religiosity is a reliable and unidimensional construct. However, the structural model revealed that ideological religiosity does not exert a significant direct effect on academic achievement (? = –0.10, p = .20). These findings suggest that deeply held religious beliefs, although central to personal identity and moral orientation, do not independently predict student performance in formal academic settings. The results reinforce theoretical perspectives that religiosity influences academic outcomes indirectly through motivation, emotional regulation, or behavioral discipline rather than as a proximate determinant. This study contributes to the growing literature on religiosity and education by isolating the ideological dimension and testing its academic relevance within a culturally homogeneous Muslim-majority context. Implications for educational practice and future research directions are discussed.